Time in Ethel Wilson's The Innocent Traveller and Swamp Angel - MacDonald, R. D. (Studies in Canadian Literature, 1988)
Ethel Wilson's novels examine time in a way that wavers between the subjective and the objective -- both perspectives are qualified and therefore balanced by the insistent existence of the other. The character Maggie thus seems wholly justified in her actions, even when they are possibly damaging to other characters; the intense -- if not constant -- subjectivity of the narrative allows the careless reader to remain mostly unaware of her potential faults. Yet at other times, the reader shares an awareness with the author that the characters in these novels do not have, that of the mysterious and infinite forces of time. Everything, ultimately, is contingent upon time, so that the characters are innocents, and so the question of will is, thematically, vitally important. Wilson's novels are worlds in which everything happens again, and yet it's never quite the same.